(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2025)
The INTRADAMS Summer School (University of Milan) combines traditional manuscript studies with advanced digital tools like multispectral imaging to analyze palimpsests. Students actively work on medieval manuscripts such as Dante’s Commedia (Triv. 1084), the Liber Primicerii, and the Fragmentum Calendarii Ambrosiani, uncovering hidden texts and documentary fragments. The program fosters interdisciplinary collaboration, enhancing both technical skills and historical knowledge.